Population of phosphate solubilizing bacteria in the liquid organic fertilizer created from palm oil bunches and pineapple rhizome: - Dermiyati Dermiyati; Radix Suharjo; Mareli Telaumbanua; Yeyen Ilmiasari; Rully Yosita; RAHMA MEULY ANNISA; ANGGI WINANDA SARI; ANIS PUJI ANDAYANI; DWI MARSENTA YULIANTI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Dermiyati, Suharjo R, Telaumbanua M, Ilmiasari Y, Yosita R, Annisa RM, Sari AW, Andayani AP, Yulianti DM. 2019. Population of phosphate solubilizing bacteria in the liquid organic fertilizer created from palm oil bunches and pineapple rhizome. Biodiversitas 20: 3315-3321. Palm oil bunches and pineapple rhizomes are abundant in Indonesia, especially in Lampung Province due to widespread agro-industrial company and they are potential to be used as sources for liquid organic fertilizer. This study was aimed to reveal microbial population within liquid organic fertilizer (LF) which was developed from palm oil bunches (PB) and pineapple rhizome (PR) and their role as phosphate solubilizing bacteria (PSB). The capability to solubilize phosphate was recorded from the clear zone area around the bacterial colony which was cultivated on Pikovskaya’s agar medium. The LF was prepared in three kinds of conditions, namely aerobic, anaerobic, and facultative an aerobic. Isolation was performed every 3 days until 24 days after incubations. The results showed that microbial population in the LF from PR was significantly higher than those developed from PB. Totally, 791 bacterial isolates were obtained from the LF; 490 isolates were achieved from PR (153 isolates from aerobic, 188 isolates from facultative anaerobic, 149 from anaerobic conditions) and 301 isolates were collected from PB (96 isolates from aerobic, 112 isolates from facultative anaerobic, 93 isolates from anaerobic conditions). In the case of isolates that were gained from PB, 166 isolates (55.15%) showed capability to degrade phosphate and 135 isolates (44.85%) did not show any capability as PSB. As for isolates obtained from PR, 269 isolates (54.90%) had capability to solubilize phosphate, meanwhile, the other 221 isolates (45.10%) did not show any capability to solubilize phosphate. Among166 isolates of PSB from PB, 60 isolates had very low capability, 55 isolates had low capability, 34 isolates had medium capability, 10 isolates had high capability and only 7 isolates had very high capability. Meanwhile, from 269 isolates of PSB obtained from PR, 135 isolates had very low capability to solubilize phosphate, 84 isolates had low capability to solubilize phosphate, 32 had medium capability to solubilize phosphate, 14 isolates had high capability to solubilize phosphate and 4 isolates produced very high capability as PSB. In total, 11 chosen isolates were selected from LF developed from both PB (7 isolates) and PR (4 isolates). Therefore, palm oil bunches and pineapple rhizomes contained PSB that can be used as LF.